2014
DOI: 10.1371/journal.pone.0097989
|View full text |Cite
|
Sign up to set email alerts
|

Testing Risk-Taking Behavior in Chinese Undergraduate Students

Abstract: The DOSPERT, developed by Weber, Blais and Betz, can be used to measure risk behaviors in a variety of domains. We investigated the use of this scale in China. The participants were 1144 undergraduate students. After we removed some items that were not homogeneous, a principal component analysis extracted six components that accounted for 44.48% of the variance, a value similar to that obtained in the analysis conducted by Weber et al. Chinese undergraduates scored higher on the investment subscale compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…The internal consistency measured was excellent (α = .94). Health risk attitude is suggested to have a moderate stability across the life span (Josef et al., 2016) or within 1 month (Du et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency measured was excellent (α = .94). Health risk attitude is suggested to have a moderate stability across the life span (Josef et al., 2016) or within 1 month (Du et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Both the original and revised versions of the DOSPERT have been used extensively across different populations (i.e., professional, student and community samples) and language groups, including a variety of European languages (e.g., French: Blais & Weber, 2006;Spanish: Horcajo, Rubio, Aguado, Hernández & Márquez, 2014;Polish: Jochemczyk, Pietrzak, Buczkowski, Stolarski & Markiewicz, 2017; German: Schmitz, Kunina-Habenicht, Hildebrandt, Oberauer & Wilhelm, 2018), and non-Euro-American samples (e.g., Chinese: Du, Li & Du, 2014;Persian: Khodarahimi & Fathi, 2016;Japanese: Krockow, Takezawa, Pulford, Colman & Kita, 2017;Hebrew: Yechiam & Telpaz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported a number of findings similar to those using Euro-American samples. For example, Chinese participants scored higher on the social and recreational risk-taking domains than the ethical, financial and health domains (Cheung & Tao, 2013), and males scored higher on the ethical, financial and health domains of the DOSPERT than females (Du et al, 2014;Hu & Xie, 2012). In terms of the level of risk-taking, Du et al (2014) reported that Chinese undergraduate students had higher scores on financial investment risk-taking, but similar scores on other domains compared to the average scores reported in Western samples.…”
mentioning
confidence: 99%